Possible versus desirable in instructional systems: who's driving? - Linda Carswell (Association for Learning Technology, 1998)
The popularity of the Internet has infected education, particularly distance education, with technological opportunism. Educators feel the 'technology pull' of Web applications and want to experiment. I have talked to colleagues from around the world, and their stories about new developments usually start with the technology, for example: 'We wanted to see what we could do with Java.' Reinhardt (1995, 55) predicts an optimistic future with improved educational productivity and qualitatively changing learning profiles - he predicts an improvement in learning due to technology alone. But do simple Internet translations of existing materials offer anything more to the student, or do we need other strategies for the effective exploitation of the Internet for teaching?